Critique of the Criminalisation of Sexual HIV Transmission - Evans, Amelia (Victoria University of Wellington Law Review, 2007)
This paper considers the extent to which people living with HIV or AIDS are liable for sexual conduct under New Zealand criminal law. After examining the ways in which the Crimes Act 1961 could be seen to criminalise sexual HIV transmission and exposure, this paper identifies two areas in which the existing law could be clarified and improved. First, by requiring a threshold "material level of risk" to be met before criminal liability is triggered and secondly by providing for disclosure as a defence where the threshold level of risk has been crossed. Clarification will ensure those people living with HIV and AIDS can knowingly act within the law. Once certainty of the law has been established, only then will social critique be viable.